EFFECT OF GTS-21, AN ALPHA7 NICOTINIC ACETYLCHOLINE RECEPTOR AGONIST, ON CLP-INDUCED INFLAMMATORY, GASTROINTESTINAL MOTILITY, AND COLONIC PERMEABILITY CHANGES IN MICE. Issue 4 (April 2016) - Nullens, Sara; Staessens, Michael; Peleman, Cédric; Schrijvers, Dorien M.; Malhotra-Kumar, Surbhi; Francque, Sven; Matteoli, Gianluca; Boeckxstaens, Guy E.; De Man, Joris G.; De Winter, Benedicte Y.
ABSTRACT: Background: During abdominal sepsis, the inhibition of gastrointestinal (GI) motility together with mucosal barrier dysfunction will lead to increased bacterial translocation and maintenance of sepsis. The activation of the vagal anti-inflammatory pathway remains an appealing therapeutic strategy in sepsis. In this respect, selective alpha7 nicotinic acetylcholine receptor (α7nAChR) agonists have shown anti-inflammatory properties in several animal models of inflammation. Methods: Sepsis was induced in OF-1 mice by cecal ligation and puncture (CLP). GI transit was quantified, and cytokine levels were determined in serum and colon. Colonic permeability was assessed by means of Evans blue injection. We studied the effect of GTS-21, an α7nAChR agonist, on the aforementioned parameters. Splenectomized animals as well as α7nAChR-knock-out animals (Chrna7 −/− ) were included to study the role of splenic macrophages and the α7nAChR during polymicrobial abdominal sepsis. Results: In septic animals, GTS-21 significantly ameliorated GI motility, lowered systemic and colonic levels of IL-6, decreased colonic permeability, and decreased the number of positive cultures obtained from blood and mesenteric lymph nodes. Splenectomy prevented animals from developing sepsis-induced ileus. Chrna7 −/− mice displayed a more severe septic phenotype, whereas GTS-21 remarkably was also beneficial in these animals. Conclusion: Our results show that peripheral targeting of the vagal anti-inflammatory pathway proves beneficial in an animal model of polymicrobial abdominal sepsis. A major role is allocated to splenic immune cells in the development of sepsis, as preventive splenectomy was protective for the development of sepsis. Data on the Chrna7 −/− mice suggest that the beneficial effects mediated by GTS-21 on inflammation and motility might be related to activation of other receptors besides the α7nAChR. Abstract : Supplemental Digital Content is available in the text